The Effects of Gender on Plasma Myostatin at Rest and in Response to Acute Resistance Exercise in Elderly Men and Women - Meysam Gholamali; Maryam Nourshahi; Mehdi Hedayati (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: The aim of this study was to investigate the effects of gender on plasma Myostatin at rest and in response to acute resistance exercise in elderly men and women. Methods & Materials: 12 healthy older men (Age=69±1.23 and BMI=23±0.3 kg/m2) and 12 healthy older women (Age=68±2.14 and BMI=23±0.4 kg/m2) volunteered for participation in this study. 72hours after the determination of muscular maximal strength (by 1-RM test), subjects participated in acute resistance exercises via 75% 1-RM. In this research, three blood samples were collected at before, immediately and 4hours after the exercise from Antecubital vein. Plasma Myostatin measured by ELISA methods. For statical analyses of research data SPPS (Ver.16) was used. Significant levels was set at P≤0.05. Results: The results of this study showed that at the rest, the amount of plasma Myostatin was significantly higher in men compared to women (t(22)=-10.90, P=0.001). Also, the amount of plasma Myostatin, in two groups, significantly decreased at immediately and 4hours after the exercise (P≤0.05). In two groups, compared to the immediately after the exercise, the amount of plasma Myostatin decreased at 4hours after the exercise, but this decrement was not significant. There was not any significant different between groups in the response of plasma Myostatin to the exercise. Conclusion: The results of this study showed that at the rest the amount of plasma Myostatin was significantly higher in the men compared to women. But in two groups, the amount of this protein decreased significantly (at immediately and 4hours after the exercise) in response to the resistance exercise. Also, this study reveled that gender has not a significant effect on the response of plasma Myostatin to resistance exercise in elderly men and women. According to the results of this study imposing a same training intervention causes same decrement in Myostatin and subsequently sarcopenia in elderly men and women.